Blow-up of solutions for a system of nonlocal singular viscoelastic equations. Issue 13 (3rd October 2018) - Zarai, Abderrahmane; Draifia, Alaeddine; Boulaaras, Salah
ABSTRACT: The main propose of this paper is to study the blow-up of solutions of an initial boundary value problem with a nonlocal boundary condition for a system of nonlinear singular viscoelastic equations. where the blow-up of solutions in finite time with nonpositive initial energy combined with a positive initial energy are shown.